2018
DOI: 10.1086/695610
|View full text |Cite
|
Sign up to set email alerts
|

The Linking Study: An Experiment to Strengthen Teachers’ Engagement with Data on Teaching and Learning

Abstract: In this AERA 2013 paper, Dr. Jonathan Supovitz investigates what it means for teachers to fruitfully use data to enhance the teaching and learning process. Informed by research on the challenges teachers face to use data meaningfully, and clues from the rich literature on formative assessment, this paper reports on the design and effects of an intervention designed to help teachers connect data on their teaching with data on the learning of their students for the purpose of informing subsequent instruction whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…The majority of the studies indicated positive effects on teacher attitudes and beliefs. Concerning attitudes and beliefs, Supovitz and Sirinides (2017) showed that the study intervention did not significantly change teachers' perceptions about the importance of instructional data or the importance of student test data or teachers' perceived proficiency using data on either teaching or assessment. However, Ebbeler et al (2017) concluded that mean scores for attitude increased more for teachers in data team schools than for teachers in the comparison group schools.…”
Section: Attitude and Belief (Personal)mentioning
confidence: 89%
See 4 more Smart Citations
“…The majority of the studies indicated positive effects on teacher attitudes and beliefs. Concerning attitudes and beliefs, Supovitz and Sirinides (2017) showed that the study intervention did not significantly change teachers' perceptions about the importance of instructional data or the importance of student test data or teachers' perceived proficiency using data on either teaching or assessment. However, Ebbeler et al (2017) concluded that mean scores for attitude increased more for teachers in data team schools than for teachers in the comparison group schools.…”
Section: Attitude and Belief (Personal)mentioning
confidence: 89%
“…Teacher development was also established through collaborative learning, for instance through collaborative discussion (Reeves & Chiang, 2018) and collaboration in data teams between colleagues, such as school leaders and a data expert from the same school (Kippers et al, 2018), teacher collaboration in professional learning communities (PLCs) (Ebbeler et al, 2017;Supovitz & Sirinides, 2017) or networked communities (Lai et al, 2009;McNaughton et al, 2012). Collaboration also took place in the format of data teams through PLCs, consisting of four to six teachers, one to two school leaders (e.g., team leaders), and a quality care manager.…”
Section: Facilitation Of Teacher Learningmentioning
confidence: 99%
See 3 more Smart Citations